Hierarchical high internal phase emulsions and transparent oleogels stabilized by quillaja saponin-coated nanodroplets for color performance. Issue 2 (26th January 2017) - Chen, Xiao-Wei; Wang, Jin-Mei; Guo, Jian; Wan, Zhi-Li; Yin, Shou-Wei; Yang, Xiao-Quan
Abstract : Herein, we report novel high internal phase emulsions and transparent oleogels that exhibit a hierarchical configuration by manipulating the spatial assembly of a natural small molecular-weight quillaja saponin for color performance. Abstract : Herein, we report novel high internal phase emulsions and transparent oleogels that exhibit a hierarchical configuration by manipulating the spatial assembly of a natural small molecular-weight quillaja saponin for color performance. Quillaja saponin (QS) is a natural triterpenoid bidesmosidic from the soapbark tree ( Quillaja saponaria Molina). Fairly monodispersed QS-coated nanodroplets (∼154 nm) were prepared using the ultrasonic emulsification strategy, and then used as block stabilizers for the fabrication of stable oil-in-water high internal phase emulsions (HIPEs, ϕ = 0.75). The resulting HIPEs can be easily converted into transparent oleogels with a very high oil loading (99.7%) through oven drying (70 °C). The jelly-like oleogels exhibit weak elastic, shear thinning behavior, good thixotropic recovery, and thermostabilization properties, which might be provided by the percolating 3D network of QS fibrils in the oil phase. We spatially tuned the color performance of the HIPEs and subsequent oleogels by locating the compositions of food colorants in different sections of their hierarchal architecture. The design and construction of hierarchical HIPEs and oleogels provide a promising new route for multitask functional delivery applications in various fields including food, cosmetics, and medical applications.